Community readiness for adolescents' overweight and obesity prevention is low in urban South Africa: a case study. (December 2016) - Pradeilles, Rebecca; Rousham, Emily; Norris, Shane; Kesten, Joanna; Griffiths, Paula
Abstract Background South Africa is undergoing epidemiological and nutrition transitions with associated increases in the incidence of overweight, obesity and diet-related chronic diseases. With the emergence of the nutrition transition in South Africa, there is an urgent need for interventions to prevent overweight and obesity in children and adolescents as risk factors for chronic diseases in adolescence may track throughout later life. This research explored the potential for faith-based organisations (FBOs) to be used as community organisations for overweight and obesity prevention interventions in adolescents by assessing the readiness of religious leaders to engage in such interventions. Methods Surveys and focus group discussions (FGDs) were conducted with 51 religious leaders in Johannesburg and Soweto. The Community Readiness Model (CRM) survey was chosen to determine the stage of readiness of this community regarding overweight and obesity prevention. Six different dimensions were assessed in the CRM (community efforts, knowledge of efforts, leadership, community climate, knowledge of the issue, resources). The surveys were scored according to the CRM protocol. The survey data were supplemented with findings from FGDs. Thematic analysis was used to analyse the FGDs. Results The mean community readiness score was 2.57 ± 0.76 which equates with the "denial/resistance stage". The mean readiness score for resources was the highest of all the dimensions (3.77 ± 0.28), followed by knowledge of the issue (3.20 ± 0.51). The lowest score was seen for community knowledge of efforts (1.77 ± 1.50), followed by community climate (2.00 ± 0.64). FGDs helped interpret the CRM scores. FGDs showed that religious leaders were enthusiastic and recognised that their role was not limited solely to spiritual guidance and mentoring, but also to physical well-being. Conclusions Religious leaders recognised that they act as role models within the community and thus have a role to play in improving adolescent health. They have some knowledge about the overweight/obesity issue and some of the resources could be made available to support overweight/obesity prevention-related initiatives. However, the low community knowledge of efforts and the negative prevailing attitude of the community towards overweight and obesity highlight the need to increase awareness of this issue prior to implementing initiatives on overweight and obesity prevention.